(untitled) - Thucydides (London, 1974)
The History of the Peloponnesian War (Greek: Ιστορία του Πελοποννησιακού Πολέμου) is a historical account of the Peloponnesian War (431–404 BC), which was fought between the Peloponnesian League (led by Sparta) and the Delian League (led by Athens). It was written by Thucydides, an Athenian historian who also happened to serve as an Athenian general during the war. His account of the conflict is widely considered to be a classic and regarded as one of the earliest scholarly works of history. The History is divided into eight books.
Keywords: Greece,Hy Lạp; History,Lịch sử; 431-404 B.C.